2008
DOI: 10.1128/aac.00175-08
|View full text |Cite
|
Sign up to set email alerts
|

VIM-15 and VIM-16, Two New VIM-2-Like Metallo-β-Lactamases in Pseudomonas aeruginosa Isolates from Bulgaria and Germany

Abstract: Two Pseudomonas aeruginosa urine isolates from Bulgaria and Germany produced two new VIM-2 variants. VIM-15 had one amino acid substitution (Tyr218Phe) which caused a significant increase in hydrolytic efficiency. The substitution Ser54Leu, characterizing VIM-16, showed no influence on enzyme activity. Both genes were part of class I integrons located in the chromosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 11 publications
1
16
0
2
Order By: Relevance
“…retrograde cystourethrography and pouchography). Although MBL-producing P. aeruginosa isolates have been sporadically reported in Germany [13][14][15], to our knowledge, outbreaks have not yet been described.…”
Section: Introductionmentioning
confidence: 64%
“…retrograde cystourethrography and pouchography). Although MBL-producing P. aeruginosa isolates have been sporadically reported in Germany [13][14][15], to our knowledge, outbreaks have not yet been described.…”
Section: Introductionmentioning
confidence: 64%
“…Metallo-enzyme producing Pseudomonas are not typical for our country. The fi rst case of VIM-positive P. aeruginosa was published in 2008 by Keuleyan et al 23 Since then till 2015 no other cases have been reported even though VIM and/or IMP encoding strains have been determined in all our neighbouring countries -Greece, Serbia, Romania and Turkey except Macedonia. [24][25][26][27][28][29] In 2013 collaboration with the Medical University of Palma de Mayorca in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Another B1 group that exhibits a similar number of variants is that of the VIM enzymes. Twelve VIM variants have been described to date, designated VIM-1 to VIM-16 [6,[34][35][36][37][38][39][40]109]. Genes encoding the IMP and VIM enzymes are found on mobile genetic elements, which facilitate their horizontal transference between different genera and species.…”
Section: Introductionmentioning
confidence: 99%